MON-LB5 A Longitudinal Cohort Study of Serum Decorin Levels in Normal and Preeclamptic Pregnant Women - Cano – Bermúdez, Maria Alejandra (J Endocr Soc, 2020)
Background: Decorin (DCN) is a leucine-rich proteoglycan that regulates diverse cellular processes such as organization and stability of extracellular matrix, extracellular signaling by the maintenance of surface receptors and growth factors and enzymes activities. Additionally, DCN is an important mediator of inflammation, angiogenesis, trophoblast migration, placentation, tumor growth and autophagy. Objective: We aimed to evaluate DCN serum levels throughout gestation in a longitudinal cohort study in normal and preeclamptic pregnant women. Methods: In this nested case-control study design within a prospective cohort of 450 pregnant women, 50 healthy and 20 preeclamptic pregnant women were followed during each pregnancy trimester and three months postpartum. Likewise, healthy non-pregnant women in the follicular and luteal phase of their menstrual cycle were included (n = 20). Serum DCN concentrations were measured by ELISA. Results: In healthy non-pregnant women, DCN levels did not differ significantly between the two stages of the menstrual cycle. On the other hand, serum DCN levels decreased significantly in both healthy and preeclamptic pregnant women in each trimester of pregnancy when compared to non - pregnant women (p <0.001) and were re-established three months postpartum (p <0.001). Moreover, serum DCN levels were significantly lower in the second trimester of gestation in normal pregnant women (p <0.05). On the other hand, serum DCN was significantly higher in preeclamptic compared to healthy pregnant women in the third trimester of pregnancy (p <0.01). Conclusion: The present study found that DCN serum levels decreased significantly throughout pregnancy in healthy and preeclamptic pregnant women. Thus, low levels of DCN may play crucial physiological and pathological roles during pregnancy. DCN has been shown to inhibit different growth factors such as vascular endothelial growth factor (VEGF), transforming growth factor-beta (TGF-β) and platelet-derived growth factor (PDGF). Hence, low levels of DCN during pregnancy might play a critical role in the control of angiogenic process.